DIMENSI AKSIOLOGIS FILSAFAT: NILAI, MANFAAT DAN TUJUAN ILMU PENGETAHUAN - Washiyyatun Hidayat, Andi Muh.; Ayu Cahyani, Mawar; Arianna, Huspa; Nur Afiqa, Andi; Rahmah, Syahidah (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2026)
Advances in science have made significant contributions to human life, but their use must be understood from the perspective of their values ​​and functions. In the study of the philosophy of science, this is discussed through axiology, which emphasizes the values, goals, and uses of science in everyday life. The purpose of this study is to analyze the axiological dimension of science from the perspective of the philosophy of science and its relationship to human life. The focus of this research is on the concept of axiology in the philosophy of science related to the values ​​and uses of science. The method applied in this study is a qualitative approach with a literature study method through the analysis of various relevant scientific literature references. The results show that the axiology of science emphasizes the importance of ethical values ​​and responsibility in the application of science so that it can bring benefits to human life. Thus, an understanding of the axiological dimension of science is essential to ensure that scientific development remains based on moral and humanitarian values.